Soil Leaching of on Particular Condition of Redox Potential by Insitu Water Source in Balandean South Kalimantan - M. ALWI; SUPIANDI SABIHAM; S. ANWAR; . SUWARNO; . ACHMADI (Jurnal Tanah dan Iklim (Indonesian Soil and Climate Journal), 2010)
The experiment was conducted in Soil Fertility Laboratory, Agriculture Faculty, IPB from March to July 2009. The treatment was arranged in Factorial Completely Randomized Design with two factors i.e. insitu water source and condition of redox potential. Water source for leaching was fresh water, peat water, and brackish water. The condition of redox potential consisted of: -100 ± 25, 0 ± 25, 100 ± 25, 200 ± 25, 300 ± 25, and 400 ± 25 mV. In leachate water on redox potential as 400 mV, the concentration of Fe2+, total Fe, SO42-, and Al were 376.76, 554.44, 961.55, and 180 ppm respectively (at first week) decreased into 227.20, 312.22, 506.86, and 44 ppm (at eight week). Whereas in leachate water that leaching by peat water, at the first week concentration of Fe2+, total Fe, SO42-, and Al were 412.50, 493.11, 823.57, and 110.50 ppm decreased into 253.65, 302.50, 463.60, and 29.50 ppm at the eighth week. After leaching as long as eighth weeks, concentration of Fe2+, total Fe, SO42-, and Al in soil material decreased from 578.26 ppm, 3680 ppm, 1011.26 ppm, and 18.66 me 100g-1 to 350.26 ppm, 3095 ppm, 376.76 ppm, and 11.79 me 100g-1.